Valuation of the Fair Market Value of the Shares of PT Link Net Tbk in Connection with the Acquisition of Shares by PT XL Axiata Tbk in 2022 Using the Discounted Cash Flow (DCF) and Abnormal Income Method - Cynthia; Lumbantobing, Rudolf; Purnama, Eka Desy (GoAcademica Research & Publishing, 2024)
Corporate takeover actions (acquisitions) carried out by companies are always in the spotlight of the capital market public, because corporate acquisition actions are classified as material transactions that require very large financing, and it is not uncommon for there to be conflicts of interest in their implementation. However, sometimes there can be cases where a company acquires another company in the hope of gaining synergies but instead incurs losses, which may be due to an unreasonable acquisition price that can harm many parties including the public and shareholders. This can of course be prevented by assessing the performance of the company to be acquired previously and assessing the company's fair market (valuation). This research was conducted to analyze the fair market value of 20% of the shares of PT Link Net Tbk in connection with the planned acquisition by PT XL Axiata Tbk using the Discounted Cash Flow and Abnormal Income methods and to analyze the price offered by PT XL Axiata Tbk to acquire 20% of the shares of PT Link Net Tbk is classified as fair or not. The research results show that in the valuation using the Discounted Cash Flow (DCF) method, based on the results of calculating the fair market value of 20% of PT Link Net Tbk amounting to IDR 2,795,896 million or IDR 4,882 per share, while in the valuation using the Abnormal Income method, it is based on the results of calculating the value fair market 20% PT Link Net Tbk amounting to IDR 2,602,704 million or IDR 4,545 per share. If we compare the transaction value of the purchase of PT Link Net Tbk shares by PT XL Axiata Tbk which is IDR 4,800 per share, the transaction value is considered fair in both methods, both the Discounted Cash Flow (DCF) and Abnormal Income methods.